Awareness of manufacturing sector towards Environment Impairment Liability (EIL) insurance policy / Norrafila Ramli - Ramli, Norrafila (Faculty of Business and Management, 2010)
The purpose of this research is to study on the awareness of manufacturing sector towards Environment Impairment Liability (EIL) insurance policy. Environment Impairment Liability insurance or EIL is one of the policies that covered liability of the policyholder against environmental risk which is excluded from general liability policy. Factors to be considered in this research are consultation by intermediaries, the need of ISO requirements and also environmental regulations compliance. Therefore, the objectives of the study described in this research were to determine the most significant factor that contribute to the awareness of manufacturing sector towards EIL insurance policy and to identify the way of these factors influence the awareness of manufacturing sector towards EIL insurance policy. This research is conducted by using non-probability sampling and the sample size are 30 respondents which are selected members under Federation of Malaysian Manufacturers (FMM). Based on the finding that conducted from this study the most significant factor that contributes to the awareness was consultation by intermediaries. Most of the respondents aware towards this type of insurance policy since it was promoted and advised by the insurance intermediaries. In conclusion, all objectives have successfully been met. Some recommendations have been suggested in order to improve the awareness of manufacturing sector towards this type of insurance policy.